NUMERICAL SOLUTION FOR FRACTIONAL PARTIALDIFFERENTIAL EQUATIONS OF TWO-SIDED - Gorial, I I (Al-Nahrain Journal of Science, 2018)
In this paper we introduce the numerical solutions of two-sided fractional partial differential equations with or without parameter. The algorithm for the numerical solution for these equations is based on finite difference method. Finally, some numerical examples are provided to show that the numerical method for solving these cases is an effective solution method.